2015
DOI: 10.1016/j.ijome.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Ocean energy development in Europe: Current status and future perspectives

Abstract: a b s t r a c tOcean energy has the potential to play a significant role in the future energy system, whilst contributing to the reduction of carbon emissions and stimulating economic growth in coastal and remote areas. Ocean energy has attracted increasing interest, particularly in the EU, which is currently at the forefront of ocean energy development.Tidal and Wave energy represents the two most advance types of ocean energy technologies. In the EU, the aim is to reach 100 GW of combined wave and tidal capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
189
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(193 citation statements)
references
References 1 publication
0
189
0
4
Order By: Relevance
“…Published estimates of wave energy LCOE vary widely [15], [18]- [20]. Several factors contribute to this variation.…”
Section: Current Estimates Of Wave Energy Lcoementioning
confidence: 99%
See 2 more Smart Citations
“…Published estimates of wave energy LCOE vary widely [15], [18]- [20]. Several factors contribute to this variation.…”
Section: Current Estimates Of Wave Energy Lcoementioning
confidence: 99%
“…Despite its potential and a surge of recent research activities focusing on numerical simulations [2]- [5], subcomponent improvements [6], [7], and integration with other renewable energy systems [8], the wave energy industry has seen comparably low commercial application in the U.S. [9] and globally [10]- [13]. The technical, environmental, and operational challenges of the wave energy industry may be analogous to those of offshore wind, though the latter has recently achieved over 14 GW of installed capacity [14] compared with less than 10 MW of wave energy [15]. The Levelized Cost of Energy (LCOE) of offshore wind has decreased along with growing capacity, approaching parity with other renewable and conventional sources [14] at a reference price of $126/MWh [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magagna et al [18] collected the information of current and proposed wave energy deployments (see Figure 1), and it can be seen that most of the installed wave energy converters have been deployed in water depths less than 50 m, and these trends can be also seen for the proposed wave farms. Similarly, Johanning et al [19] indicated early that wave energy converters will be very likely installed in the shallow to intermediate depths typically at the 50 m contour in the open areas for wave energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Note: the size of the bubble refers to the capacity of installed projects (full circle) or the maximum site capacity (circles). Source: courtesy of Davide Magagna [18].…”
Section: Introductionmentioning
confidence: 99%